Teachers’ Beliefs and Practices Towards Language Assessment in an Indonesian Islamic University - Muhammad Nur Akbar Rasyid (Langkawi: Journal of The Association for Arabic and English, 2022)
In recent decades, assessment design and implementation issues have been a severe concern in teaching and learning English as a Foreign Language (EFL). Language assessment, which is inextricably linked to EFL teachers' conceptions and education, influences students and their learning. This case study investigates teachers' underlying beliefs concerning EFL assessment as well as their practices in the classrooms of Indonesian Islamic universities. The study engaged ten university EFL teachers who work in an Indonesian Islamic Higher Education institution. The participants were recruited using the purposive sampling technique. Semi-structured interviews were used to determine teachers' beliefs about language assessment. Thematic analysis was used to transcribe, code and segment data to establish themes, categories, and subcategories that depict participants' beliefs regarding EFL assessment. The findings revealed that the participants used various terms to describe assessment, providing an exciting background to their practices. They also believed in language assessment's varied purposes, including administrative and pedagogical purposes. Most participants conceived assessment as an extension of EFL classroom teaching and learning, thus significantly impacting student learning and approaches to learning. Therefore, considering how assessments enhance student learning would influence teachers' decision-making. This paper also describes the implications of these findings for better governance of institutional systems for assessing English as a Foreign Language